Origin of Phu Quoc ridgeback dog by using mitochondrial d-loop sequences - Dung, Tran Hoang; Quan, Thai Ke; Cong, Nguyen Thanh; Hieu, Huynh Van; Dung, Chung Anh (Academia Journal of Biology, 2016)
Phu Quoc ridgeback dog is among valuable dog breeds of Vietnam with precious characteristics, such as smart, good health, friendly to human and most importantly, still keeping some features of wild hunting dogs. The purpose of this research is to evaluate the genetic diversity in order to trace the origin of Phu Quoc ridgeback dogs. D-loop region on mitochondrial genome of seventy-seven samples of Phu Quoc ridgeback dogs and thirty samples of village dogs (as control) have been analysed and showed that Phu Quoc ridgeback dogs have high genetic diversity. Phu Quoc ridgeback dogs have an unusually high frequency of haplotype E, particularly 16.88% with haplotype E1 and 9.10% with haplotype E4. Furthermore, Phu Quoc ridgeback dog also has ancestor haplotypes, such as B1 (19.48%) and C2, C3 (respectively 9.10 and 7.79%). Normal dogs have general haplotype A, B and C, in which two ancestor haplotype A1 and B1 shares the highest proportions (20 and 16.67% respectively). Especially, there is no village dog sample carried haplotype E as found in Phu Quoc ridgeback dogs. Analysing the phylogenetic tree showed that Phu Quoc ridgeback dogs have a close relationship to dogs originated from East Asia (China, Japan and Korea). The hypothesis of migration and ridgeback formation processes of Phu Quoc ridgeback dogs has been addressed and discussed.